RANTAI PASOK DAN NILAI TAMBAH KERIPIK NANGKA PADA AGROINDUSTRI KERIPIK PANDA ALAMI DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Rini Yunita Sari; Ali Ibrahim Hasyim; Sudarma Widjaya (Lampung University, 2018)
This study aims to analyze the flow pattern of supply chain of jackfruits, supply chain performance, supply chain efficiency, and calculate the added value products of Jackfruits chip in Panda Alami Agroindustry. This study is conducted purposely in Panda Alami Agroindustry in Gedong Tataan Sub-district of Pesawaran District. The data is collected in Februari 2017, performance measurements are made by comparing measurement indicators with FoodSCOR Card indicators. Efficiency calculations are performed using a software deap 2.1, the calculation of value added is done by Hayami added value method. The result showed that the flow pattern starting from the farmers as the main raw material supplier. The performance of the supplier of Panda Alami Agroindustry was good, based on compared value of FoodSCOR card. Efficiency measurements indicated that only 37.5 percent of supply chain actors were already efficient for DMU farmers’ category, and 100 percent efficient for retail and agroindustry category. The calculation of the added value of jackfruits chips of Panda Alami Agroindustry showed positive value, it meant that agroindustry was feasible to be developed.Key words: added value, agroindustry, efficiency, farmers, jackfruits, performance